MUHAMMAD IBN âABD AL-WAHHÃB DAN GERAKAN WAHABI - Mangasing, Mansur (Institut Agama Islam Negeri (IAIN) Palu, 2008)
In the Islamic world, in the middle age, the ideas on reformation and the efforts of purification of akÃ®dah hadÂ emerged. This was a reaction against the extant political condition and tauhid comprehension of Muslims. InÂ Arab, a chief figure, Muhammad ibn âAbd al-WahhÃ¢b who possessed a great concern towards the matter of akÃ®dah purification of Muslims and Islamic reformation, emerged. The efforts of al-WahhÃ¢b finally developed into a movement called the Wahabiyyah Movement. The main target of this movement was to purify Muslimsâ akÃ®dah that had been mixed with heretics. Kata Kunci: Â Â Muhammad ibn âAbd al-WahhÃ¢b, Gerakan Wahabi, pemurnian Islam, pembaruan Islam